Livres, escravos e a construção de um conceito moderno de criminalidade no Brasil Imperial - Ferreira, Ricardo Alexandre [UNESP] (FapUNIFESP (SciELO), 2009)
In the last decades, has become common, building sources based in police and judicial records in historic research. In Brazilian historiography the issue most significantly marked by this phenomenon was the enslavement of Africans and their descendants. With special attention to the construction of the sources analyzed in such studies, this article aims to understand and interpret the role given by members of the Imperial Brazilian State to the freeman and slave in the picture of building a modern concept of criminality. To reach this objective, besides the penal codes, we analyzed the reports issued by the Ministers of Justice. Trying to contribute to the debate expert, this study asserts that, despite the perpetuation of slavery after the political independence of the country, many were the circumstances in which distinction between the freeman and the slave went not expressed.
Freemen, slaves and the construction of a modern concept of criminality in Brazil Imperial
Keywords: Criminality; Freedom; Imperial Brazil; Slavery